Grazing land parcels for joint village land use planning in Kiteto, Kilindi, Mvomero and Chalinze landscapes - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing grazing land parcels allocated in village land use plans in Chalinze, Kiteto, Kilindi and Mvomero districts, Coastal (Pwani), Tanga, Morogoro and Manyara regions, Tanzania in 2018.